Factors Affecting Third-party Funds in Indonesian Sharia Banks: A Meta-analysis - Rachma Indrarini; Novi Febriyanti (Shirkah: Journal of Economics and Business, 2025)
While Indonesia, with its substantial Muslim population, holds promise for the advancement of Islamic banks, the current reality reveals that the volume of third-party funds for these banks in the country trails significantly behind that of conventional banks. This study aims to determine the determinants of third-party funds in Indonesian Islamic banks. This quantitative study used meta-analysis. The data were derived from accredited national journals and were subsequently processed using OpenMEE. The findings of this study indicate a positive correlation between third-party funds and various variables, such as inflation, exchange rates, BI Rate, GDP, SBI, JCI, FDR, CAR, NPF, BOPO, profit sharing and bonuses, promotional costs, ROA, LDR, money supply, service offices, and total assets. The results of this study can serve as a reference for practitioners of Islamic banks when formulating policies pertaining to the increase in third-party funds.